2022
DOI: 10.1002/art.42249
|View full text |Cite
|
Sign up to set email alerts
|

Three Months of Glucocorticoids in Rheumatoid Arthritis: A Bridge Too Short?

Abstract: Since their invention, glucocorticoids (GCs) have always been regarded as special. Hailed as a "miracle drug" after Philip S. Hench demonstrated astonishing effects in a patient with severe rheumatoid arthritis (RA) in 1948, pioneering physicians quickly realized that extended therapy with high doses carried a high risk of adverse events (AEs). Hench received his Nobel prize only 2 years later (1), and in his acceptance lecture he enumerated a comprehensive list of AEs before proposing a sensible approach and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Finally, the recent CORRA trial showed that GC bridging with an initial dose of 60 mg/day, tapered to zero in 3 months, briefly suppressed disease activity but had no effect on damage progression at 1 year compared with MTX monotherapy [ 31 ]. In other words, bridging protocols with a maximum period of 3 months as recommended by the EULAR are suboptimal [ 32 ].…”
mentioning
confidence: 99%
“…Finally, the recent CORRA trial showed that GC bridging with an initial dose of 60 mg/day, tapered to zero in 3 months, briefly suppressed disease activity but had no effect on damage progression at 1 year compared with MTX monotherapy [ 31 ]. In other words, bridging protocols with a maximum period of 3 months as recommended by the EULAR are suboptimal [ 32 ].…”
mentioning
confidence: 99%